Does Tax-Benefit Linkage Matter for the Incidence of Payroll Taxes? - Bozio, Antoine; Breda, Thomas; Grenet, Julien; Guillouzouic, Arthur (Review of Economic Studies, 2026)
Abstract We analyse earnings responses to six large payroll tax and income tax reforms in France. Our findings indicate full pass-through to workers when there is a strong and transparent link between contributions and expected benefits. In contrast, employer payroll taxes with no tax-benefit linkage exhibit limited pass-through to workers, while income tax nominally borne by employees show nearly full pass-through. Together with a meta-analysis of the literature, we interpret these results as empirical support for the long-standing hypothesis that tax-benefit linkage matters for the incidence of payroll taxes. In the absence of such linkage, our findings suggest that the individual-level incidence of payroll taxes aligns with their statutory incidence.